Is Stimulated Thyroglobulin Necessary after Ablation in All Patients with Papillary Thyroid Carcinoma and Basal Thyroglobulin Detectable by a Second-Generation Assay? - Pedro Weslley Rosario; Gabriela Franco Mourão; Maria Regina Calsolari (International Journal of Endocrinology)
Objective. To evaluate the percentage of elevated stimulated thyroglobulin (sTg) and persistent or recurrent disease (PRD) in patients with detectable basal Tg < 0.3 ng/mL. Methods. The sample consisted of 130 patients with papillary thyroid carcinoma (PTC) who were at low risk of PRD and who had neck ultrasound (US) without abnormalities, negative anti-Tg antibodies (TgAb), and detectable basal Tg < 0.3 ng/mL about 6 months after ablation. Results. sTg was <1 ng/mL in 88 patients (67.7%), between 1 and 2 ng/mL in 26 (20%), and ≥2 ng/mL in 16 (12.3%). Imaging methods revealed the absence of tumors in 16 patients with elevated sTg. During follow-up, Tg increased to 0.58 ng/mL in one patient and lymph node metastases were detected. Sixty-nine patients continued to have detectable Tg < 0.3 ng/mL and US revealed recurrence in only one patient. Sixty patients progressed to persistently undetectable Tg without apparent disease on US. Conclusions. In low-risk patients with PTC who have detectable basal Tg < 0.3 ng/mL after ablation, negative TgAb, and US, persistent disease is rare and eventual recurrences can be detected by basal Tg elevation and/or subsequent US assessments, with follow-up without sTg being an “alternative” to Tg stimulation.